Effect of acute stress and variation of the chewing stimulus on somatic nociceptive pain in a murine model - Aguirre-Siancas, Elías Ernesto (2023)
Acute stress is related to the energetic release of catecholamines, cytokines, and cortisol, which trigger pain perception. Chewing stimulates serotonergic neurons, these neurons modulate the neural pathways of pain; however, the relationship between these variables is still in the process of understanding. Objective. To determine the effect of acute stress and chewing stimulus on pain. Methods. an experiment that was developed in the Faculty of Medicine of the UNMSM. 40 eight-week-old male Balb/c mice were randomly assigned into 5 equal groups. A: week 1 without any stimulus and week 2 chewing stimulus + stress. B: week 1 without any stimulus and week 2 stress. C: week 1 stress and week 2 without any stimulus. D: week 1 masticatory stimulus + stress and week 2 without any stimulus. E: control, without any stimulus. Pain was assessed in the 5 groups at 7 and 14 days using the tail-withdrawal time test before thermal stimulation. Results. The ANOVA test was used for the intergroup evaluation, finding no significant difference. Using the t student test for related samples, the intragroup evaluation was made, where a significant difference was found between 7 vs. 14 days, both in group A (p=0.029) and in group C (p=0.03). Conclusion. The effect of acute stress on pain perception was decreased by chewing stimulus in Balb/c mice.